Interferensi Bahasa Asing dalam Tuturan Bahasa Indonesia Mahasiswa Universitas Peradaban - Prameswari, Ikhya Aulia (Lembaga Yasin AlSys, 2025)
The phenomenon of foreign language use in students’ utterances, particularly English and Korean, is increasingly present in both academic and everyday communication and gives rise to interference that has the potential to affect the structure and normative rules of Indonesian. This study aims to identify and analyze the forms and causal factors of foreign language interference in the utterances of students at Universitas Peradaban. A descriptive qualitative approach was employed, with data collected through participant observation and semi-structured interviews. The data were analyzed using a linguistic analysis approach by classifying interference into phonological, morphological, syntactic, and lexical aspects. The findings show that the most dominant interference occurs at the lexical level, characterized by the direct use of English words or phrases without translation, such as deadline, submit, and mute, as well as syntactic deviations resulting from the influence of foreign sentence structures. The main factors causing interference include habitual use of foreign languages in course materials, the influence of digital media, and the perception that using foreign languages reflects a higher level of intellectuality. In conclusion, foreign language interference in students’ utterances is not only a linguistic phenomenon but also reflects social and cultural dynamics within the academic environment. The implications of this study underscore the need to strengthen awareness and guidance regarding the proper use of Indonesian in higher education in order to maintain the identity and function of Indonesian as the national language amid the pressures of globalization.